Enhancing the field of view of a distributed-cavity laser incorporating cat-eye optics by compensating the field-curvature. (July 2022) - Sheng, Quan; Wang, Aihua; Wang, Meng; Ma, Hanchao; Qi, Yue; Liu, Junjie; Wang, Sijia; Xu, Degang; Shi, Wei; Yao, Jianquan
Highlights: The receiver field of view (FoV) of a distributed-cavity laser incorporates cat-eye optics was investigated. We found that the field curvature (FC) significantly impacts FoV when the laser incorporates long working distances. The effect of FC can be compensated by choosing proper lens and mirror parameters, or by using a customized aspheric lens. We proposed three different optimized cat-eye designs with FC corrected. An aperture-limited FoV of over ±20° was realized. Abstract: The influence of field curvature (FC) on a distributed-cavity laser incorporating cat-eye optics was theoretically and experimentally investigated. We found that the FC can defocus the cat-eye and seriously limit its field of view (FoV), since the cavity stability region becomes very narrow at long working distances of several meters. Three improved cat-eye designs are demonstrated, in which the FC-induced defocusing was compensated by choosing off-the-shelf components with appropriate parameters or by using a customized aspheric lens. With these new designs, a distributed-cavity diode-end-pumped Nd:YVO4 laser was capable of operating efficiently within a large receiver FoV of ±20°, which was an order of magnitude larger than that achieved prior to optimization (using a traditional cat-eye design), at a long working distance of 5 m. The effectiveness and robustness of these new designs pave the way for alignment-free lasers with long-distributed-cavities, which are essential for resonant laser charging applications.